Estudo de efeitos de nanopartículas de prata sobre as propriedades espectroscópicas de vidros cálcio boroaluminato dopados com európio - Sandrini, Marcelo (2016)
This work presents a study about the silver (Ag) incorporation in Calcium Boroaluminate (CaBAl) glasses, as well as the use of thermal treatment as a means of nucleation and growth of Ag nanoparticles (AgNPs) and their consequences on the luminescent properties of europium-doped CaBAl glasses. To ensure that the thermal treatment process does not result in optical quality loss and/or crystallization on the studied glasses, the glass transition temperature (Tg) (∼610 ◦C) was used as reference. Thus, the adopted temperatures were 550, 575 and 600 ◦C. Optical absorption results demonstrated the incorporation of Europium trivalent ions and the nucleation of Ag nanoparticles in the treated samples. By excitation/emission maps, it was possible to verify the existence of characteristic emission centers of Eu3+ transitions (5D0-7Fj , j = 1, 2, 3 e 4) and emission centers of silver optically active species, which have broad emission band covering almost the entire visible region in the electromagnetic spectrum. The emission spectra under excitation at 325 nm initially showed an increase in the emission intensity as function of thermal treatment time, due to the fact that the treatment can promote the formation of Ag0-Ag+ and Ag+-Ag+ pairs. However, the reduction of the emission intensities observed for longer treatment or higher temperatures indicates a competition between the AgNPs formation process and the formation of Ag pairs. Emission spectra under excitation at 442 nm, resonant with the surface plasmon resonance (SPR) band, indicated that the plasmon resonance effect, from AgNPS, provides a new excitation region for the silver pairs. An amplification of the emission intensity was observed and can be associated with the SPR effect and/or the energy transfer processes between AgNPs and optically active species.By the chromaticity coordinates (x, y) in the CIE 1931 diagram, the color correlation temperature (CCT) and color rendering index (CRI), it was verified that the Eu2O3-AgNO3-co-doped CaBAl glasses have promising characteristics for application in devices emitting white light and the choice of composition, as well as the conditions of thermal treatments can work as tools for tuning the color of emission.